Business Plan ENT 300 : Lailai Chicken Rice Restaurant / Muhamad Syamir Saifulizan … [et al.] - Saifulizan, Muhamad Syamir; Hamuda Azhar, Nayli Hafizah; Mazlan, Nur Syazwanie; Zulkefli, Nursabrina; Hamsani, Nurul Syazwani (2021)
LaiLai Chicken Rice Restaurant is a business that offers scrumptious food and the most importantly to be Malaysia's No. 1 Chicken Rice restaurant. Initiated by Nayli Hafizah binti Hamuda Azhar as the owner of the restaurant who loves to eat chicken rice. We are planning to choose Pt 218, Jalan Kompleks, Bandar Kota Bharu, 15300, Kota Bharu, Kelantan as our strategic location to start our business. Our chicken rice is unique because we serve rainbow coloured rice. To those who are chicken rice lover, they should try our Rainbow Chicken Rice product which is guaranteed to be extremely delicious. For our Rainbow Chicken Rice, we were using fresh or original ingredients. Furthermore, our signature rainbow rice is made from natural food colouring because we want our customers to feel the originality itself. LaiLai Chicken Rice was established at Kota Bharu, Kelantan. Price of our Rainbow chicken Rice in size medium is RM10.00 We expected that our business will become more developed soon because with our signature dish, the demand will increase not only during promotion day but in daily basis. This will give more advantages for us to open our branches across the country and we can improve it to more profitable and capable in long run.